Gaucher Disease: A First Reported Adult Case in Indonesia - Ardhi Rahman Ahani; Cosphiadi Irawan; Agnes Stephanie Harahap; Klara Yuliarti; Maria Francisca Ham; Faramitha Nur Izzaty; Damayanti Rusli Sjarif (Acta Medica Indonesiana)
A 44-year-old female presented with a distended abdomen and fatigue. On physical examination, prominent splenomegaly was found. The laboratory investigations revealed pancytopenia and decreased albumin-globulin ratio. The abdominal ultrasonography revealed splenomegaly, cholelithiasis, and cystitis, and the bone survey showed osteopenia. Differential diagnoses included leukemia, multiple myeloma, and myelofibrosis therefore bone marrow puncture was performed. However, histopathologic examination found Gaucher-like cells in the bone marrow aspiration. The finding of CD68 positivity in Gaucher-like cells by using the immunohistochemistry staining supporting Gaucher disease. To confirm the diagnosis, an examination of glucocerebroside substrate from the patient’s blood plasma was performed. Glucosylsphingosine, a deacylated form of glucosylceramide, was markedly elevated. Therefore, the diagnosis of Gaucher disease was confirmed. This is the first reported adult Gaucher case diagnosed in Indonesia.